Are we ready for education in Metaverse? PLS-SEM analysis - Nguyen, Binh-Hai Thi; Dang, Tri-Quan; Nguyen, Luan-Thanh; Tran, Thuy-Thanh Thi (Edelweiss Applied Science and Technology, 2024)
The objective of this study is to investigate the adoption of met-averse education in Ho Chi Minh City, Vietnam, by employing the Theory of Planned Behavior (TPB) as the foundational theoretical framework. Metaverse education, utilizing immersive and interactive virtual environments for educational objectives, is an innovative and auspicious methodology in the contemporary digital realm. Data collection was conducted via judgmental sampling. Partial least squares structural equation modeling was used for the analysis. The results suggest a significant and positive impact of Consumer Intention (CI) on the practical use (AU) of the met-averse in the field of education. Furthermore, the factors of Perceived Behavioral Control (PBC), Subjective Norm (SN), and Perceived Value strongly influenced Consumer Intention (CI) in a positive manner. Moreover, Emotional Value (EV) and Social Value (SV) had a substantial impact on the Perceived Value (PV) of using the metaverse in educational contexts. Nevertheless, the lack of statistical significance in the relationship between Attitude towards Behavior (ATB) and Consumer Intention (CI) is recognized. This research not only addresses a significant gap in the theory of IS literature but also offers valuable insights for educators, policymakers, and developers. If you really understand the things that make people open to metaverse education, you can make big changes to plans and actions that are used to successfully add metaverse education to the regular school setting, especially in Ho Chi Minh City, Vietnam.